2020
DOI: 10.1111/wej.12596
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nucleation and crystal growth of calcium carbonate in hard waters using Paronychia arabica in an arid desert region

Abstract: The formation of CaCO 3 of groundwater has important implications in the industry. Many conventional scale inhibitors are considered environmentally unfriendly. In this study, we investigate the effect of aqueous extract of Paronychia arabica (PA) as new green antiscalant agents on the precipitation of CaCO 3 in an arid desert region. The antiscaling properties of these extracts towards CaCO3 formation were tested using chronoamperometry (CA), electrochemical impedance spectroscopy (EIS) and Fast Controlled Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…According to Karar et al (2020) chronoamperometry was used in another attempt to study the effect of a new green antiscalant agent, also known as the aqueous extract of paronychia Arabica (PA) on the precipitation of CaCO 3 in a desert area. When using the concentration of 150 mg/L of green extract, the results have shown that scaling was completely inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…According to Karar et al (2020) chronoamperometry was used in another attempt to study the effect of a new green antiscalant agent, also known as the aqueous extract of paronychia Arabica (PA) on the precipitation of CaCO 3 in a desert area. When using the concentration of 150 mg/L of green extract, the results have shown that scaling was completely inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the presence of the extract reduces the amount of scale deposited on the entire surface of the electrode. This inhibitor can be used for groundwater in conventional electrochemical cells with three electrodes, where the water temperature can reach 32 • C. It was observed that, at concentrations of 80 ppm of the PA extract, there is a partial inhibition of the CaCO 3 deposition and when the concentration of the inhibitor was increased to 150 ppm, no scale was formed [39].…”
Section: Complexing Agents and Other Inhibitors Of Precipitationmentioning
confidence: 99%